TMIC-52. REACTIVE ASTROCYTES AID THE EVOLUTION OF IMMUNOSUPPRESSIVE ENVIRONMENT AND DRIVE ONCOGENIC SIGNALING IN GLIOBLASTOMA. (11th November 2019) - Heiland, Dieter; Ravi, Vidhya; Behringer, Simon P; Wurm, Julian; Beck, Juergen; Schnell, Oliver
Abstract: Reactive astrocytes are caused by multiple pathologies of the central nervous system, whereby they undergo distinct transcriptomic re-programming. Although the role of reactive astrocytes in some inflammatory diseases has been investigated, many central questions regarding the immunoregulatory functions of tumor-associated astrocytes and their crosstalk to microglia remain poorly understood. In our presented study, we purified astrocytes from various pathologies and different brain tumors to map the transcriptional landscape of reactive astrocytes. We identified the marker genes CHI3L1 and CD274 highly enriched in reactive astrocytes of the marginal astrogliosis scar at the tumor boarder. Human neocortical slices along with a microglia loss-of-function model were used to explore the crosstalk of microglia and reactive astrocytes within the tumor environment. Our results revealed that the reactive phenotype mutually arises from both, microglia and tumor cells. This interaction caused JAK/STAT signalling in reactive astrocytes along with a large release of anti-inflammatory cytokines such as TGFß and IL10. Additionally, inhibition of the JAK/STAT pathway recovered the release of anti-inflammatory cytokines and resulted in a pro-inflammatory environment. Besides the immunosuppressive properties, we found evidence that reactive astrocytes drove AKT and MAPK signaling in the tumor through astrocytic released CHI3L1 and consequential binding to IL13RA2. Our findings revealed increased malignant properties arising from astrocytic-tumor interaction, which were rescued by IL13RA2 inhibition. In a nutshell, reactive astrocytes have decisive regulatory tasks in the microenvironment of CNS tumors. Along with microglia, reactive astrocytes cause the evolution of an immunosuppressive environment and support malignant properties of the tumor.